2017
DOI: 10.1177/2156587217722474
|View full text |Cite
|
Sign up to set email alerts
|

Management of Breast Milk Oversupply in Traditional Persian Medicine

Abstract: Comprehensive explanation about milk oversupply is not available in the current literature because few studies have been done on this topic. In traditional Persian medicine, milk oversupply and its management have been described. The aim of this study was to investigate milk oversupply from the perspective of medieval Persian practitioners. In this study, some main medical resources of traditional Persian medicine such as Al-Havi and the Canon of Medicine were studied to extract valuable information about milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Traditionally, caraway oil has been used to help people to avoid phlegm, relieve constipation, and provide urination control. Nursing mothers use caraway to increase the flow of breast milk [17]. Many pharmacological potencies of caraway seeds have been demonstrated such as anti-convulsant, antimicrobial, analgesic, anti-inflammatory, anti-anxiety, anti-hyperglycemic, and anti-spasmodic properties, and it has been used as a cure for dyspepsia, flatulent indigestion, diarrhea, and hysteria [18].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, caraway oil has been used to help people to avoid phlegm, relieve constipation, and provide urination control. Nursing mothers use caraway to increase the flow of breast milk [17]. Many pharmacological potencies of caraway seeds have been demonstrated such as anti-convulsant, antimicrobial, analgesic, anti-inflammatory, anti-anxiety, anti-hyperglycemic, and anti-spasmodic properties, and it has been used as a cure for dyspepsia, flatulent indigestion, diarrhea, and hysteria [18].…”
Section: Introductionmentioning
confidence: 99%
“…The smart recommendation of Persian Medicine includes consumption of almond, hazelnut, pistachio, and wheat which are among rich foods, highlighting the greater necessity of paying attention to the recommendations of this old medicine (23). Previous studies conducted in Iran showed that, these foods are more specific to lactation than other foods and increase the amount of milk (24). Thus, further studies are suggested to be conducted on the effect of consumption on lactation.…”
Section: Discussionmentioning
confidence: 99%
“…In Persian Medicine, in addition to recommending the use of many useful foods, avoiding of some foods during breast-feeding period has been recommended. This may be due to changes in taste or volume of milk (24). Different studies have also prohibited consumption of some foods for breast-feeding mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding unnecessary consumption of galactogogues, including traditional foods that may contain galactogogues (e.g., herbal teas, curry sauces spiced with fenugreek, soups containing moringa) (Levels 4 and 1). 6,14,15 Misconception that healthy term infant feeding volumes will increase significantly beyond the initial 6 weeks of life. Cultural expectations about normal infant feeding and sleeping patterns.…”
Section: Behavioral Interventionsmentioning
confidence: 99%
“…24 Other less widely used herbs, but which are utilized more regionally, include basil, caraway, and parsley (Level 4). 15…”
Section: Abm Protocol 131mentioning
confidence: 99%